Caracterização mineralógica de Latossolos em diferentes feições do relevo na região de Jaboticabal, SP - Montanari, Rafael; Marques Júnior, José [UNESP]; Campos, Milton César Costa; Souza, Zigomar Menezes De; Camargo, Lívia Arantes [UNESP] (Universidade Federal do Ceará, 2010)
Different surface land form expressed by the relief can cause variations in soil properties in different magnitudes, depending mainly on a specific location in the landscape. Therefore, the objective of this study was to make the mineralogical characterization of Oxisols in different relief forms in the region of Jaboticabal, SP. Three trenches were opened in the convex, linear and concave landforms, done morphological description of the soil horizons and collected soil samples for physical, chemical and mineralogical characterization. It was found that the oxidic mineralogy is dependent on the type of landform, with the dominance of goethite on the concave landform and hematite on the linear landform. The desferrific clay minerals exhibited dominance of gibbsite in the concave, compared to convex and linear landforms that were dominated by the kaolinitic mineralogy.

As diferentes feições da superfície terrestre, expressas pelo relevo, são capazes de provocar variações nos atributos do solo em magnitudes diferenciadas, dependentes, principalmente, de um local específico da paisagem. Sendo assim, o objetivo deste trabalho foi realizar a caracterização mineralógica de Latossolos em diferentes feições do relevo na região de Jaboticabal, SP. Foram abertas três trincheiras nas pedoformas convexa, linear e côncava e, em seguida, foram realizadas a descrição morfológica dos horizontes e coleta de solo para caracterização física, química e mineralógica. Constatou-se que a mineralogia oxídica é dependente do tipo de pedoforma, com dominância de goethita na pedoforma côncava e a hematita dominou em pedoforma linear. Os minerais da fração argila desferrificada exibiram domínio de gibbsita na pedoforma côncava, em comparação as pedoformas convexas e lineares que predominam a mineralogia caulinítica.
Characterization mineralogical of Oxisol in different relief form in the region of Jaboticabal, SP
Keywords: Landscape form; Pedogenesis; Soil mineralogy; Forma da paisagem; Pedogênese; Mineralogia do solo